2013
DOI: 10.1073/pnas.1219548110
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of α -pinene secondary organic material and implications for particle growth and reactivity

Abstract: Particles composed of secondary organic material (SOM) are abundant in the lower troposphere. The viscosity of these particles is a fundamental property that is presently poorly quantified yet required for accurate modeling of their formation, growth, evaporation, and environmental impacts. Using two unique techniques, namely a "bead-mobility" technique and a "poke-flow" technique, in conjunction with simulations of fluid flow, the viscosity of the water-soluble component of SOM produced by α-pinene ozonolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
584
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(651 citation statements)
references
References 60 publications
43
584
5
Order By: Relevance
“…At cool and/or dry conditions, however, we assume that highly viscous OA effectively shields BaP from heterogeneous oxidation, similar to that observed for eicosane (a highly viscous solid organic) coatings (18) (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). This approach is consistent with highly viscous SOA observed at dry conditions (27,28), persistence of highly viscous SOA at cooler temperatures in the free troposphere (26), and also higher viscosity of complex SOA mixtures (29) that are likely more atmospherically relevant compared with laboratory-generated SOA (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). We show that including the shielding of BaP by OA results in better agreement with BaP measurements in the field, promotes stronger long-range transport, and also produces greater global incremental lung cancer risk (ILCR) estimates due to exposure to PAHs, compared with the default model that neglects this shielding by OA.…”
supporting
confidence: 77%
“…At cool and/or dry conditions, however, we assume that highly viscous OA effectively shields BaP from heterogeneous oxidation, similar to that observed for eicosane (a highly viscous solid organic) coatings (18) (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). This approach is consistent with highly viscous SOA observed at dry conditions (27,28), persistence of highly viscous SOA at cooler temperatures in the free troposphere (26), and also higher viscosity of complex SOA mixtures (29) that are likely more atmospherically relevant compared with laboratory-generated SOA (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). We show that including the shielding of BaP by OA results in better agreement with BaP measurements in the field, promotes stronger long-range transport, and also produces greater global incremental lung cancer risk (ILCR) estimates due to exposure to PAHs, compared with the default model that neglects this shielding by OA.…”
supporting
confidence: 77%
“…(b) Measured viscosity (left axis) of extracted a-pinene SOA. 36 Bulk diffusion coefficient (right axis) is obtained through the Stokes-Einstein equation. (c) Evolution of total mass concentration of initially 300 nm diameter particles at different RH under net growth conditions.…”
Section: Hygroscopic Growth Timescale Of Soamentioning
confidence: 99%
“…81,82 The size-dependent data support the hypothesis that SOA particles from ozonolysis of trans-3-hexene are initially formed by nucleation of higher molecular weight oligomers (n Z 4) and then grow via condensation of shorter oligomers and other less oxygenated, more volatile species. 12,30,31,38,39 Phase state of SOA The phase of atmospheric particles (liquid/solid) plays a crucial role in various physical and chemical processes of particles such as growth, 49,50,52 aging, 47,48,52,53 and water uptake. 48,51 In the present study, particle impaction/ATR-FTIR measurements were performed to offer some insight into the phase/viscosity of trans-3-hexene SOA since the impaction patterns on the Ge crystal have been shown to be an indicator of phase.…”
Section: This Journal Is © the Owner Societies 2015mentioning
confidence: 99%
“…We report here an expanded investigation of the ozonolysis of trans-3-hexene in which particle composition is probed as a function of size. In addition, the influence of water vapor, OH and SCI scavengers, as well as the phase state of SOA particles (which plays critical roles in various physical and chemical processes of aerosols) [47][48][49][50][51][52][53][54][55][56] are elucidated and possible mechanisms are examined in light of predictions of a box model for this system. Initial studies of the ozonolysis of the much larger and complex biogenic alkene a-cedrene are also reported, and it is shown that the mechanism of particle formation for this sesquiterpene is different from that for trans-3-hexene.…”
Section: Introductionmentioning
confidence: 99%